Cervical ribs in human early life: morphological variability and first identification as a morbidity criterion in a past population. Issue 1 (18th March 2020) - Partiot, Caroline; Guillon, Mark; Peressinotto, David; Castex, Dominique; Maureille, Bruno
Abstract: Despite the medical literature on supernumerary cervical ribs in extant adult samples, little is known about their development and occurrence in early infancy. The documentation of cervical ribs in modern samples of fetuses and neonates is indeed affected by ethical as well as technical limitations. The aim of the present study was to investigate their frequencies and morphological variability in the first known archaeological collection of very young children with this anatomical variant. The study sample comes from the 8B‐51 necropolis on the Saï island (Sudan) and dates to the Classic Kerma Period (XVIIIe–XVIe centuries BC). It consists of 64 individuals deceased between 24 weeks of amenorrhoea and 2 years of age. Bilateral or unilateral cervical ribs were found in 27 individuals. A total of 43 cervical ribs were identified, 38 of which are fully preserved. According to these observations, at least 42% of the individuals have unilateral or bilateral cervical ribs, with an average maximum length of < 1 cm. This frequency is very high compared to those observed in contemporary adult samples (up to 3%). First, the comparison of our results with biological and genetic research demonstrating the link between the occurrence of cervical ribs and a reduced chance of survival during infancy allows the first identification of this trait as an indicator of morbidity in an archaeological collection, a morbidity to which a genetic homogeneity or even endogamy could contribute. Second, the number of ribs studied makes it possible to propose a morphological classification based on the general shape and the shape of the articular facets, classification that can be used tos refine the analyses of the trait in future samples. Abstract : The first known archaeological collection of neonates and infants with cervical ribs allows us to investigate the morphological variability of this trait in early life, and its frequencies in a past population. Based on the results of biological and genetic literature, we show that this trait appears to be an indicator of morbidity in the sample. We propose a morphological classification that can be used to refine the analyses of the trait in future studies.